Bilateral Paramedian Thalamic Infarction Initially Presenting as a Convulsive Seizure - Jianping Wang; Xiaojie Fu; Chao Jiang; Hengfang Liu; Yuanzheng Zhao; Wei Han (Case Reports in Neurological Medicine)
Bithalamic infarctions initially presenting as a convulsive seizure are rarely reported and, to our best knowledge, have never been reported in China. Here, we present a patient with convulsive seizure at the onset of bilateral paramedian thalamic infarction. The diffusion-weighted imaging revealed that the infarct area is supplied by Percheron artery. Associated with the relationship between seizure and centrencephalic system and reticular formation as previously reported, we suggest that seizure could be the onset symptom of paramedian thalamic infarction. Physicians should recognize this condition, because both seizure control and early ischemic stroke management are required.